Pengaruh Penggunaan Instagram Sebagai Media Komunikasi @starbucksindonesia terhadap Citra Merek Pasca Boikot Pro Israel - Feli Samudra; Muhamad Sopyan (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2026)
This study aims to analyze the influence of the @starbucksindonesia account's use of Instagram as a communication medium on brand image following the pro-Israel boycott. The boycott arose from Starbucks' alleged involvement in the Israeli-Palestinian conflict, which triggered a decline in its reputation and negative sentiment among Indonesians. In this situation, Instagram, as a visual-based social media platform, was utilized as a primary means of shaping public opinion and responding to the crisis. The study employed a quantitative approach using an online questionnaire survey. Respondents were 100 followers of the @starbucksindonesia Instagram account, aged 18–35, and former Starbucks customers. Data analysis was conducted using validity and reliability tests, simple linear regression, t-tests, and coefficients of determination using SPSS version 27. The results showed that all research instruments were valid and reliable. The main finding demonstrated that Instagram use had a statistically significant effect on Starbucks' brand image. The coefficient of determination value indicated a strong relationship, indicating that the majority of changes in respondents' perceptions were influenced by communication via Instagram. This research supports the Uses and Effects theory, which states that social media not only serves as an information provider but also has the ability to shape consumer perceptions and attitudes. Therefore, Instagram plays a strategic role in digital communications for crisis management and brand image restoration.